2015
DOI: 10.1007/s40194-015-0245-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of welding position on properties of duplex and superduplex stainless steel circumferential welds

Abstract: The influence of welding position on properties of duplex and superduplex stainless steel welds was studied. Circumferential pipe welds were produced using mechanised gas metal arc welding in flat position, vertical up position and overhead position. Dilution, corrosion resistance, mechanical properties, microstructural features and weld imperfections were assessed and related to the welding position. Welds produced in flat and vertical up positions were less likely to produce porosity than those welded in ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The selection of the shielding gas for GMAW welding was initially based on previous research [12,13]. However, a recent study [14] and preliminary trials in this project confirmed that small amounts of arc stabilizing components (O 2 , CO 2 ) in the shielding gas caused porosity in superduplex multi-pass welds with more than 3 passes.…”
Section: Materials and Welding Experimentsmentioning
confidence: 99%
“…The selection of the shielding gas for GMAW welding was initially based on previous research [12,13]. However, a recent study [14] and preliminary trials in this project confirmed that small amounts of arc stabilizing components (O 2 , CO 2 ) in the shielding gas caused porosity in superduplex multi-pass welds with more than 3 passes.…”
Section: Materials and Welding Experimentsmentioning
confidence: 99%
“…Using the models used for model validation, the predicted yield strength according to the chemical composition variation due to dilution between the high-Mn steel and the three welding consumables, listed in Table 8, is as shown in Figure 5. Because the dilution rate varies depending on the welding position, current, speed, and heat input [40][41][42], the heat input per unit length was fixed at 10 kJ/cm. In model validation, the accuracy of the model developed through multiple regression analysis was the highest; however, the R 2 and MAPE of machine-learning-based prediction models may be lowered depending on the attributes and quantity of data points.…”
Section: Dilution and Yield Strength Of Stainless-steel-based Weld Me...mentioning
confidence: 99%
“…Using the models used for model validation, the predicted yield strength according to the chemical composition variation due to dilution between the high-Mn steel and the three welding consumables, listed in Table 8, is as shown in Figure 5. Because the dilution rate varies depending on the welding position, current, speed, and heat input [40][41][42], the heat input per unit length was fixed at 10 kJ/cm. The stepwise linear regression and linear SVM models showed similar trends for various material combinations and dilutions; however, they exhibited slight differences compared with the multiple regression model, which had the highest prediction accuracy.…”
Section: Dilution and Yield Strength Of Stainless-steel-based Weld Me...mentioning
confidence: 99%
“…Welding position affects mainly heat input which is the most significant factor during any hardfacing operation since it directly affects the welding dilution. Many previous studies show the influence of heat input on dilution and wear resistance [9,10]. Zhao et al [11] have observed the influence of heat input on the grain size and hardness, and have found that higher hardness could be resulted due to finer grain size.…”
Section: Introductionmentioning
confidence: 99%